CONTAMINANT ADSORPTION CHARACTERISTICS OF KYUSHU REGIONAL SOILS - Yan Jun Du; Shigenori Hayashi; Takenori Hino; Kenta Tanaka (International Association of Lowland Technology, 2000)
Four types of Kyushu regional soils, Ariake clay, Haido, Akaboku, and Diatom earth were selected to evaluate their capacities of contaminant adsorption. The contaminants presented in this study are there types of single-salt solutions, KCL, NaCL, and CaCL2 respectively. A batch-type test was performed for each soil and Freundlich model was adopted to plot adsorption isotherms. It was found that among the tested soils. Ariake clay has the highest adsorption capacity in the case of K+ and Ca2+ ions, whereas Diatom earth fails to adsorb any cation. Based on the adsorption isotherms, the cation selectivity of each soil was given. It is concluded that the contaminant adsorption capacity of clay soil is significantly affected by the soil cation exchange capacity (CEC). For a given soil, it seems that the mobility of the cation of the interested species when it transports through soil is mainly controlled by the cation replaceability, its initially adsorbed concentration and nature of the soil, provided that the other conditions remain constant.